Sistematización de experiencias en los procesos de gestión documental en el distrito de educación en el cantón Sigchos - Calo Quinaucho, María Blanca (2019)
The present research work describes the current analysis of the processes of Document Management; they are applying to the chronological-alphabetical file systems in the Administrative-Financial and of Human Talent area from District of Education at Sigchos Canton. The problem that was evidenced is the lack of documentary management processes into the institution considered important documents for the development of this that prevents a correct manipulation of the documentation since the production until the final disposition. These present problems and delays in the administrative activities, which imply in the reduction of the productivity and inefficiency of the staff. This analysis will help the entity to design improvement strategies in the Document Management processes that favors the permanence and efficiency of the same, in addition of becoming extensive to other areas of the organization. The methodology that was been used the descriptive and non-exploratory research in base to the lived practice and got techniques by obtaining information from various sources, such as internal documents of the institution, observations, interviews, the results analysis were optimal, due to: if a document management process, this did not know in depth about the subject, still. Finally, it is concluded that the process of document management, both physically and digitally, are necessary for information, because it will help in the optimization of the administrative processes. They are recommended that the document management processes such as an administrative strategy in order to reduce, optimize the time of the administrative staff and improve the attention to the general public.